(untitled) (Innovate Conferences, 2025)
This study investigates the impact of integrating boxing techniques and training methods into the physical preparation curriculum of cadets at the Ministry of Internal Affairs Academy. A 12-week experimental program was designed and implemented with two groups: a control group receiving standard physical training and an experimental group receiving an enhanced boxing-based regimen. The research evaluates improvements in strength, endurance, agility, and reaction speed through pre- and post-assessments using standardized military fitness tests. The results demonstrate a statistically significant improvement in the experimental group, suggesting that the inclusion of boxing methods effectively enhances overall physical fitness. The study contributes to the development of modernized physical training protocols suitable for law enforcement personnel.